"Actual Political Affiliations Are of Secondary Importance": Communism and Women's Entangled Loyalties in the Australian Anti‐Nuclear Movement, 1945–65. (30th November 2022) - Viney, Hannah
Abstract : The 1950s in Australia began with the newly elected Menzies Government's campaign to ban the Communist Party of Australia, feeding into and sustaining growing anti‐communist rhetoric in the post‐war nation. Fears of communist infiltration coloured the actions of the Australian peace movement, with public commentators and political figures condemning the movement as a communist fifth column intent on destroying Australian society. Peace activists had to manage such perceptions of their work while navigating their own beliefs on politics and ideology. Using the women of the anti‐nuclear movement of the 1950s and 1960s as a case study, this paper demonstrates that while the movement would often be publicly characterised — both in contemporary sources and more recent literature — as divided along ideological lines, individual alliances were far more complex and entangled. Though Cold War divisions appeared to be upheld in public nuclear disarmament sentiment, private sentiments were far more nuanced. These women had to decide what was more important to them: the cause or the image. Ultimately, for many, communism was a pressing issue, but nuclear disarmament was more pressing still.